2013
DOI: 10.1111/1467-8489.12037
|View full text |Cite
|
Sign up to set email alerts
|

Valuing public and private urban tree canopy cover

Abstract: In this paper, we estimate the effect of tree canopy cover on sales price of urban residential properties in Perth, Western Australia. Using a data set of 5606 single family homes sold in 2009 and a spatial hedonic model with three spatial effectsspatial-temporal lag on dependent variable, spatial error, and spatially lagged independent variables -we estimated the location-specific effect of tree canopy cover. Tree canopy cover increases the property value when located on adjacent public space, but decreases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Home buyers or renters' willingness to pay for a particular level of environmental quality is revealed when other house, property and neighbourhood features are held constant (Anthon, et al, 2005;Baranzini, 2008;Conway, et al, 2010;Donovan and Butry, 2010;Escobedo, et al, 2015;Garrod and Willis, 1992b;Glaesener and Caruso, 2015;Kong, et al, 2007;Mansfield, et al, 2005;Melichar, et al, 2009;Pandit, et al, 2014;Pandit, et al, 2013;Panduro and Veie, 2013;Payton, et al, 2008;Sander, et al, 2010;Saphores and Li, 2012;Tyrväinen, 1997).…”
Section: Methods Of Valuing Esmentioning
confidence: 99%
See 4 more Smart Citations
“…Home buyers or renters' willingness to pay for a particular level of environmental quality is revealed when other house, property and neighbourhood features are held constant (Anthon, et al, 2005;Baranzini, 2008;Conway, et al, 2010;Donovan and Butry, 2010;Escobedo, et al, 2015;Garrod and Willis, 1992b;Glaesener and Caruso, 2015;Kong, et al, 2007;Mansfield, et al, 2005;Melichar, et al, 2009;Pandit, et al, 2014;Pandit, et al, 2013;Panduro and Veie, 2013;Payton, et al, 2008;Sander, et al, 2010;Saphores and Li, 2012;Tyrväinen, 1997).…”
Section: Methods Of Valuing Esmentioning
confidence: 99%
“…However, studies of the effect of street trees on property values have reported significant variations between and within cities (Anderson and Cordell, 1988b;Donovan and Butry, 2010;Drake-McLaughlin and Netusil, 2010;Pandit, et al, 2014;Pandit, et al, 2013;Wachter and Bucchianeri, 2006). This suggests that seeking a generic property value algorithm for international versions of "i-tree" may be as inappropriate as the one in the US version of "iTree Streets" which is based on the results of one 1988 study of front-yard trees in Athens, Georgia (Anderson and Cordell, 1988).…”
Section: The Research Problemmentioning
confidence: 99%
See 3 more Smart Citations